Tribological Characteristics Improvement of Wear Resistant MAO-Coatings. (19th June 2013) - Malyshev, V. N.; Volkhin, A. M.; Gantimirov, B. M.
Abstract : Currently, the most promising technology of coating formation is microarc oxidation (MAO) with unique properties of the surface layer, which combine high wear resistance, corrosion resistance, and heat and erosion resistance. Microarc oxidation can be used for parts and components manufacturing in various segments of industries. However, the technology improvement by improving the tribological characteristics of MAO-coatings can not only enhance economic effect, but also expand its application.